2020
DOI: 10.1111/nph.16897
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation in rice Fertilization Independent Endosperm 1 contributes to grain width under high night temperature stress

Abstract: A higher minimum (night-time) temperature is considered a greater limiting factor for reduced rice yield than a similar increase in maximum (daytime) temperature. While the physiological impact of high night temperature (HNT) has been studied, the genetic and molecular basis of HNT stress response remains unexplored. We examined the phenotypic variation for mature grain size (length and width) in a diverse set of rice accessions under HNT stress. Genome-wide association analysis identified several HNT-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 114 publications
(148 reference statements)
0
31
0
Order By: Relevance
“…HNT donor identification should consider NSC dynamics during grain filling phase in addition to heading and maturation, in order to get a more precise estimation of remobilization, as NSC can re‐accumulate before maturation (Wang et al, 2017). Few previous studies on the genetic basis of HNT have been reported (see Dhatt et al, 2021). Our GWAS for stem remobilization traits in 2018DS identified a set of candidates for NSC concentration harvest under control conditions, which is different from the results reported by Wang et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…HNT donor identification should consider NSC dynamics during grain filling phase in addition to heading and maturation, in order to get a more precise estimation of remobilization, as NSC can re‐accumulate before maturation (Wang et al, 2017). Few previous studies on the genetic basis of HNT have been reported (see Dhatt et al, 2021). Our GWAS for stem remobilization traits in 2018DS identified a set of candidates for NSC concentration harvest under control conditions, which is different from the results reported by Wang et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a clear evidence for a positive role of the locus Fertilization Independent Endosperm ( Fie1 ), a component of the Polycomb Repressive Complex 2 (FIS‐PRC2) complex, for mature grain size under HNT was reported identified by genome‐wide association studies and by testing overexpression lines and knockout mutants (Dhatt et al, 2021).…”
Section: Molecular Responses To Hntmentioning
confidence: 99%
“…In embryo: AC, axial cell; BC, basal cell; COL, coleoptile; EP, embryo proper; P1, leaf stage 1; RAM, root apical meristem; SU, suspensor; SCU, scutellum; SAM, shoot apical meristem. Crops and heat stress references: rice—[1] (Chen et al, 2016); [2] (Dhatt et al, 2020); [3] (Folsom, Begcy, Hao, Wang, & Walia, 2014); [4] (Paul et al, 2020); [5] (Begcy, Sandhu, & Walia, 2018); tomato—[6] (Iwahori, 1966); bush bean—[7] (Ormrod, Woolley, Eaton, & Stobbe, 1967) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Post‐fertilization and Early Embryogenesismentioning
confidence: 99%
“…A recent study analysed early grain development (1–10 days after fertilization) in rice subjected to high night temperature (28°C) that generally affects rice grain chalkiness (Dhatt et al, 2020). This study further identified FIE1 as a key regulator of grain width since knockout mutants recorded decreased grain size under high night temperature (Dhatt et al, 2020).…”
Section: Post‐fertilization and Early Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation